Perhitungan Beban Pendinginan Mobil Box Pengangkut Ikan Beku - Suyanto, Suyanto (Marine Science and Technology Journal; Vol 4 No 1 (2023): Marine Science and Technology JournalDO - 10.31331/maristec.v3i2.2518, 2023)
Fish is the main product of marine catches which is widely consumed to meet food needs. Fish is a product that is easily damaged or spoiled, especially at room temperature conditions. Transport must be carried out with care so that fishery products are not exposed to high temperatures during loading and transportation of transport vehicles. One thing that needs to be considered in using a box truck fleet as a means of transportation for transporting frozen fish is choosing the right cooling machine capacity. This study aims to calculate the cooling load on box trucks for transporting frozen fish. With the resulting total cooling load and the proportion of cooling load can be a consideration in selecting the cooling machine used in the car cooler. From the existing analysis data, the total cooling load of a frozen fish transport truck box with box dimensions of 250cm x 170cm x 165cm and a total load of 1200kg of fish is 5531 Watts. The cooling machine recommended for use in frozen fish transport box trucks requires a cooling machine with a power of 2 PK.